Parsimonious edge-coloring on surfaces - Sarah-Marie Belcastro (Electronic Journal of Graph Theory and Applications (EJGTA), 2018)
We correct a small error in a 1996 paper of Albertson and Haas, and extend their lower bound for the fraction of properly colorable edges of planar subcubic graphs that are simple, connected, bridgeless, and edge-maximal to other surface embeddings of subcubic graphs.